Organizational social context and academic achievement of youth in residential care: The mediating role of youth-caregiver relationship quality - Silva, C. S. (2022)
Existing research examining the academic performance of youth in residential care has often overlooked the contextual factors contributing to youth achievements. Guided by an ecological perspective, this study aimed to investigate the associations between various dimensions of residential care settings’ (RCS) organizational social context (i.e., organizational climate, structure, and work attitudes) and youth's academic achievement, considering the mediating role of youth-caregiver relationship quality in those associations. The study was based on a sample of 699 young people aged 12–25 (M = 16.18; SD = 2.07), and their respective main residential caregivers (N = 242) and case managers (N = 168), from 55 RCS in Portugal. Given the hierarchical structure of the data, analyses were performed using multilevel modelling. Results showed that the association between caregivers’ reports of the residential care setting organizational social context, specifically regarding caregiver engagement and centralization (i.e., authority hierarchy), and youth's academic achievement (i.e., higher scores in Math and Portuguese language) was mediated by lower levels of negative interactions with caregivers, reported by the youth. The findings demonstrate the need for an ecological, multilevel perspective, in addressing youth's academic achievement in residential care. Awareness and appropriate resources should be directed at improving child-caregiver relationship quality and social climate of RCS, among other efforts, to improve poor academic performance of youth in residential care.